The Effect of Entrepreneurship and Character Learning on Student Entrepreneurial Interest in Makassar City - Syam, Agus; Jufri, Muhammad; Sikar, Muhammad Alfa; Sudarmi, Sudarmi (Jurnal Moral Kemasyarakatan, 2025)
This study aims to examine the impact of entrepreneurship education and entrepreneurial character on the entrepreneurial intention of students in Makassar City. Entrepreneurship education in Indonesia faces significant challenges in the era of the Fourth Industrial Revolution, where most of the material taught is still theoretical and less applicable to the current generation's practical needs. Research shows that students desire more practical learning, such as business internships and digital technology training, that align with market developments. In Makassar, with a high unemployment rate among university graduates, entrepreneurship education is expected to create a generation capable of competing and creating jobs, especially through the rapidly growing Micro, Small, and Medium Enterprises (MSMEs) sector. This study employs an explanatory quantitative approach with regression analysis to test the influence of entrepreneurship education and entrepreneurial character on entrepreneurial intention. Data were collected through observation, questionnaires, interviews, and documentation with a Likert scale. The results show that both factors have a significant impact, with entrepreneurial character contributing more to students' entrepreneurial intentions. Therefore, strengthening entrepreneurship education in higher education is crucial to fostering students' entrepreneurial intentions and competencies.